PATHOLOGICAL ASPECTS ASSOCIATED WITH COVID-19 IN PATIENTS WITH HEPATITIS - Mamadaminov Abdullo Azimjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: COVID -19 ( coronavirus Disease 2019 - the disease caused by the new coronavirus 2019) continues to pose a threat to public health around the world. Epidemiological evidence suggests that patients with metabolic disorders and chronic diseases are most susceptible to SARS - CoV -2 (severe acute respiratory syndrome coronavirus 2). Among possible factors of organ damage, systemic hyperimmune inflammation due to a “ cytokine storm”, cytopathic effects, hypoxia, drug toxicity, etc. are considered.